A Step Forward Towards Exploring Nutritional and Biological Potential of Mushrooms: A Case Study of Calocybe gambosa (Fr.) Donk Wild Growing in Serbia - Jovana Dragan Petrovic; Ângela Fernandes; Dejan Stojković; Marina Soković; Lillian Barros; Isabel C.F.R. Ferreira; Aditya Shekhar; Jasmina Glamočlija (Polish Journal of Food and Nutrition Sciences)
Edible mushrooms have been appreciated globally for their organoleptic, nutritional and chemical properties. In the present study, fruiting body of Calocybe gambosa , wild growing in Serbia, has been chemically characterized (content of macronutrients, soluble sugars, tocopherols, fatty and organic acids) and its bioactive (antimicrobial and antioxidant) properties were evaluated. The results obtained suggest that this mushroom is a source of carbohydrates and proteins (72 g/100 g dry weight (dw) and 16 g/100 g dw, respectively), with a low fat content (1.5 g/100 g dw). Sugar analysis revealed the presence of trehalose (3.82 g/100 g dw) and mannitol (0.22 g/100 g dw). Tocopherol composition revealed the presence of α-tocopherol (7.8 μg/100 g dw), while fatty acid analysis revealed the presence of 24 fatty acids with the prevalence of polyunsaturated fatty acids. Amongst organic acids, oxalic, quinic, malic, citric and fumaric acid were detected (2.8 g/100 g dw, 1.45 g/100 g dw, 11.3 g/100 g dw, 1.3 g/100 g dw, 0.08 g/100 g dw, respectively). Comprehensive antioxidant activity analysis (reducing power, DPPH radical scavenging activity, β-carotene/linoleate and TBARS assays) indicate that the mushroom is a perspective antioxidant source, whereas its antimicrobial potential turned out to be moderate. Nevertheless, at a sub-inhibitory level, the methanolic extract disrupted cell-to-cell communication using Pseudomonas aeruginosa PAO1 as a model system. Finally, enrichment of oatmeal cookies with C. gambosa flakes not only improved their nutritional value, but was praised among the participants in sensory evaluation test, indicating that along with results of chemical composition and biological activity, this mushroom has a potential to be regarded as functional food.